2012
DOI: 10.3340/jkns.2012.52.6.513
|View full text |Cite
|
Sign up to set email alerts
|

Medial Loop of V2 Segment of Vertebral Artery Causing Compression of Proximal Cervical Root

Abstract: ObjectiveIt is rare that the medial loop in the V2 segment of the vertebral artery (VA) causes compression of the proximal cervical root of the spinal cord without leading to bony erosion and an enlarged foramen. We evaluated the clinical significance and incidence of the medial loop in the V2 segment of the VA.MethodsWe reviewed the records from 1000 consecutive patients who had undergone magnetic resonance imaging evaluation of the cervical spine between January 2005 and January 2008. The inclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The vertebral artery, originating from the subclavian, passes through the transverse foramina of the C2-C6 vertebrae in the cervical spine, and is referred to as the V2 segment in this region [1]. The limited space for the artery to traverse may result in anomalies or vascular abnormalities causing either compression of the artery (with symptoms of vertebrobasilar insufficiency) or compression of the cervical nerve roots (resulting in pain or radicular symptoms) [2].…”
Section: Historical Review Of the Condition Epidemiology Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…The vertebral artery, originating from the subclavian, passes through the transverse foramina of the C2-C6 vertebrae in the cervical spine, and is referred to as the V2 segment in this region [1]. The limited space for the artery to traverse may result in anomalies or vascular abnormalities causing either compression of the artery (with symptoms of vertebrobasilar insufficiency) or compression of the cervical nerve roots (resulting in pain or radicular symptoms) [2].…”
Section: Historical Review Of the Condition Epidemiology Diagnosismentioning
confidence: 99%
“…The limited space for the artery to traverse may result in anomalies or vascular abnormalities causing either compression of the artery (with symptoms of vertebrobasilar insufficiency) or compression of the cervical nerve roots (resulting in pain or radicular symptoms) [2]. An anomalous V2 segment may present as a tortuous vertebral artery; a medial location of the vertebral artery or an abnormal vertebral artery entrance [1]. Hadley was the first to report a tortuous vertebral artery loop with bony erosions in the cervical vertebrae of four out of 21 cadavers [3].…”
Section: Historical Review Of the Condition Epidemiology Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Reports 10,11 regarding the prevalence and anatomical features of patients with those medial loop of arteries based on magnetic resonance angiography (MRA) suggested that only a few patients showed higher anatomical risk for VAI in ACDFs. The relationship between arteries and bone or uncovertebral joint to which surgeons pay most attention to during the decompression procedure is, however, unclear based on MRA.…”
mentioning
confidence: 99%